1993
DOI: 10.1093/ajcn/57.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Dietary carbohydrate, muscle glycogen, and exercise performance during 7 d of training

Abstract: The effects of moderate- or high-carbohydrate diets on muscle glycogen and performance in runners and cyclists over 7 consecutive days of training were determined. Muscle biopsies were performed on 4 separate days before exercise for 1 h at 75% peak oxygen consumption (VO2) followed by five, 1-min sprints. After the training session on day 7, subjects ran or cycled to exhaustion at 80% peak VO2. Muscle glycogen for cyclists and runners was maintained with the high-carbohydrate diet but was reduced 30-36% (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 16 publications
5
42
2
Order By: Relevance
“…Whilst these findings do not support the results of the aforementioned studies, these data are in agreement with the findings of Sherman and colleagues (Sherman et al, 1993) who investigated the effects of moderate vs. high carbohydrate diets on training capacity and high intensity exercise performance. These authors reported that although intensified training on a moderate carbohydrate diet resulted in significant reductions in muscle glycogen compared with the high carbohydrate diet, no differences in high intensity exercise performance were observed.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Whilst these findings do not support the results of the aforementioned studies, these data are in agreement with the findings of Sherman and colleagues (Sherman et al, 1993) who investigated the effects of moderate vs. high carbohydrate diets on training capacity and high intensity exercise performance. These authors reported that although intensified training on a moderate carbohydrate diet resulted in significant reductions in muscle glycogen compared with the high carbohydrate diet, no differences in high intensity exercise performance were observed.…”
Section: Discussionsupporting
confidence: 80%
“…Sherman and colleagues investigated the effects of a high (10 g/kg/day) vs. moderate (5 g/kg/day) carbohydrate diets on muscle glycogen levels during 7 days of intense cycling (Sherman et al, 1993). The authors reported that the moderate carbohydrate diet resulted in a significant reduction in muscle glycogen over time (30-36%) compared with the high carbohydrate diet (Sherman et al, 1993). Interestingly however, no difference in a maximal test to exhaustion was observed after the 7-day intensified training period compared to pre-trial, or differences between carbohydrate groups.…”
Section: Introductionmentioning
confidence: 99%
“…The question as to what constitutes an 'adequate' CHO intake has been addressed by several recent studies (Lamb et al 1990;Simonsen et al 1991;Sherman et al 1993). The general consensus is that providing athletes are ingesting 5-6 g CHO · kg -1 body mass · day -1 , they are probably not compromising their training capacity.…”
Section: What Do Athletes Eat and What Should They Eat During Training?mentioning
confidence: 99%
“…Pre-exercise muscle glycogen was not dierent between diet conditions in that study. In a study by Sherman et al (1993), high-intensity exercise performance (running or cycling performance at 80% O 2max until exhaustion; total exercise time approximately 10 min) was not dierent following 7 consecutive days of intense cycling or running training on a moderately low CHO diet (5 g CHO á kg A1 á day A1 , approximately 40% CHO) compared to similar training on a high CHO diet (10 g CHO á kg A1 á day A1 , approximately 80% CHO) despite dierences in pre-exercise muscle glycogen concentration (for cyclists, muscle glycogen concentrations before and after the training sessions were 187 and 70 mmol á kg A1 wet tissue, respectively, and for runners, 107 and 74 mmol á kg A1 wet tissue, respectively).…”
Section: Introductionmentioning
confidence: 98%
“…In contrast to the above, most recent studies in which the eects of diet on the capacity to perform high-intensity exercise are examined have used trained subjects and less extreme diet manipulations than the early studies: the majority of these have failed to produce signi®cant dierences in performance (Ratz et al 1989;Sherman et al 1993;Hargreaves et al 1997). Ratz et al (1989) found no dierence in high-intensity exercise performance (7 W á kg A1 on a cycle ergometer to exhaustion) lasting approximately 1 min between those subjects on a normal mixed diet and those on a CHOloading regimen.…”
Section: Introductionmentioning
confidence: 99%